Synthesis and characterization of new mono and bis thiazolidine-2,4-dione derivatives - Tan, Glenn Kelly Uy (Animo Repository, 2015)
Mono and bis Thiazolidine-2,4-dione (TZD) derivatives (Ia, Ib, IVa, VII, VIIIa and VIIIc) with nonpolar moieties were synthesized and characterized. The synthesis of O-substituted TZD derivatives (Ib and VIIIc) involves the preparation of palkoxybenzaldehyde precursors (P1b and P8c) followed by condensation reaction with TZD. Compounds Ib and VIIIc were obtained in 47.55 and 12.58% yield respectively. The synthesis of TZD derivatives Ia, IVa, VII, and VIIIa involves the reaction of 5-(4-hydroxybenzylidene)thiazolidine-2,4-dione (A) with either alkyl halides or alkyl tosylates with varying lengths of nonpolar groups or linkers. This coupling reaction produced the target compounds Ia (5.78%), IVa (5.38%), VII (3.16%), and VIIIa (2.34%). The nonpolar moieties were incorporated to increase lipophilicity of the compounds and make the molecules better penetrate the cell membrane. Hopefully, this will lead to an increase in biological activity. Cytotoxic activity using PrestoBlueÂ® assay were carried out on compounds Ia, Ib, IVa, VII, VIIIa and VIIIc against colorectal carcinoma (HCT-116), colorectal adenocarcinoma (HT-29), breast adenocarcinoma (MCF-7) and primary human dermal neonatal fibroblast (HDFn) cell lines. All compounds did not show cytotoxic activity in normal cells having no treatment concentration to inhibit at least 50% of the total number of HDFn cells unlike Bleomycin with an IC50 of 21.724 Î¼g/mL. Compound Ib exhibited cytotoxic activity against HCT-116 (IC50: 23.711 Î¼g/mL), HT-29 (IC50: 28.841 Î¼g/mL)and MCF-7 (IC50: 31.303 Î¼g/mL) cancer cell lines, which are comparable to Bleomycin (HCT-116, IC50: 28.237 Î¼g/mL HT-29, IC50: 26.955 Î¼g/mL MCF-7, IC50: 24.207Î¼g/mL). Moreover, Ia and VII were comparable to Bleomycin against HCT-119 and HT-29 with IC50 values of 25.618 Î¼g/mL and 32.259 Î¼g/mL, respectively. These compounds may be potential candidates as an anti-cancer drug.